(untitled) - Dorson, Richard M. (Tokyo, Rutland, Vt., 1962)
This is a completely charming book, one that can be picked up at random and read either for your own pleasure or for that of your children. Lafcadio Hearn may have been the discoverer for the Western world of the fertility of Japanese legends.
Keywords: Tales; Japan